Challenges and complexities in remediation of uranium contaminated soils: A review. (December 2018) - Selvakumar, Rajendran; Ramadoss, Govindarajan; Mridula P. Menon,; Rajendran, Karuppuli; Thavamani, Palanisami; Ravi Naidu,; Megharaj, Mallavarapu
Abstract: Uranium contamination of soil has been a major concern with respect to its toxicity, accumulation in the food chain and persistence in the environment. Owing to these problems, remediation of uranium-contaminated soils has been investigated by various techniques. This review focuses on the challenges and complexities associated with the remediation of uranium-contaminated soil at field level. Therefore, laboratory studies have been excluded from this review. Challenges faced during remediation of uranium-contaminated soil using various techniques such as microbial/phyto/chemical/material based strategies have been discussed with suitable examples. Various factors that have a major influence on uranium decontamination process in soil such as soil type, uranium speciation, the presence of coexisting ions and organics, etc., have been highlighted. This review brings out the significance of the integrated role of various factors which determine the efficiency of the uranium decontamination process. Highlights: Uranium contamination of soil has been a major concern. Remediation of uranium-contaminated soils investigated by various techniques. Challenges faced and complexities in remediation discussed. Significance of the integrated role of various factors in uranium decontamination process.